The Biophysical Modelling of the Stress Theory - Vincze, Janos; Vincze-Tiszay, Gabriella (Advances in Social Sciences Research Journal, 2023)
Selye published a short note about his findings in Nature in 1936. Selye applied his famous theory of stress to everyday life. A stress-free state is equivalent to being dead. In our paper we write about the some directions in stress research and the stress syndromes in clinical medicine. We show that eustress suits to situations when the psychoneuroendocrine stimulation of the organism and its behavior is temperate, maintaining at an optimal level the physical and mental resources and the health status and inducing a positive adaptation to the environment. We give a comparative analysis between the eustress and distress. Psychical stressors are those which come into being independently from the man’s will and destroy – as social factors – psychic and organic components taking place in the response, the organism consequently get tired. During the harmonic life gradually all human psycho-organic components shall get exhausted. Forming a biophysical model is not the task of the biologist or physicist alone, a good model can successfully constructed only by common, collective-work. This is typically the task of the biophysicist and a problem which falls within the competence of this discipline. Model is always an approximation, the user of the model has to take into consideration that he can approach only the absolute truth just through the endless series of relative truths. We use the Le-Chatelier principle and determine the measure of psychical organization.